Perancangan Sistem Perhitungan Debit Air Otomatis Berbasis Internet of Things pada PDM Tirta Garut - Ayu Latifah Latifah; Yosep Septiana; Abdul Aziz Nurhakim (APIC, 2021)
The service process in calculating water discharge for PDAM customers is still using conventional water meters as a result, the process of delivering information cannot be optimally accepted by various related parties and often the process that occurs requires officers to directly visit the customer's place then automatically manually recorded, the results from conventional meters and are often wrong in recording and calculating, of course this requires a solution. This research was carried out with the aim of changing the current conventional water discharge calculation system to be automatic using a Microcontroller and based on IoT as a solution that can be done from the current problems for calculating water discharge. The design method used is the Prototype Model from Sommerville, with Listen to Customer stages / listen to complaints for system needs, Build / Revise mock-ups to design and create systems and Customer test drive mock-ups to test the system that has been made and use Unifed modeling. Modeling Language for system representation in an easy-to-understand picture. This research produces tools and applications that can calculate water discharge automatically with integrated data using Internet of Things technology, apart from that, web application media are designed to provide information to customers and companies regarding the amount of usage along with the amount of bills charged to customers. customer. who can provide solutions to problems in PDAM Tirta Garut.